PENGARUH TAI BERBANTUAN KARTU POP UP KR-CHART TERHADAP HASIL BELAJAR SISWA SMAN 2 SINGKAWANG - Puspita, Vivi Anugrah; Muharini, Rini; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this study were to determine the difference of students learning  achievement taught using TAI type with pop up KR-chart card media which taught using conventional learning, and to determine its effect toward  student learning achievement for the eleventh grade MIA students in SMA Negeri 2 Singkawang. This study used quasi experimental design. According to simple random sampling technique, two classes of eleventh grade MIA students in SMA Negeri 2 Singkawang, were selected as sample they were XI MIA 1 as experiment and XI MIA 2 as control class. The instrumens of collecting data in this research were learning achievement tests, observation sheets, and interview guidelines. The final test results data were analyzed using Whitney U-mann test which obtained the Sig. (2-Tailed) value of 0.001 < 0.05. The analysis results showed that there were differences in learning achievement between students taught using TAI type with pop-up KR-chart cards media and students taught using conventional models. Learning TAI with pop-up KR-chart card media on solubility and solubility product material had an effect of 32.89% on student learning achievement with an Effect Size value of 0.91 in which categorized high. Keywords:  Learning  Achievement, Pop Up Key-Relation Chart, Solubility and Solubility Product, Team Assisted Individualization